Impact of grape pomace on growth performance, carcass traits and meat colour in broiler chickens: Insights from a meta-analysis - Freddy Manyeula (Poultry Science)
Grape pomace (GP) is a by-product from grape juice and wine production that is rich in potentially beneficial phytochemical compounds. Accordingly, several studies have been conducted to evaluate the effect of including GP in broiler chicken diets on a range of parameters that include growth performance, carcass traits, and meat quality. However, reported results have been inconsistent. Therefore, this meta-analysis investigates the effects of GP on Average daily feed intake (ADFI), average daily gain (ADG), feed conversion ratio (FCR), carcass traits, and meat quality in broiler chickens. The objective is to identify knowledge gaps and create new insights using published data. Twenty (20) research articles on the topic were identified via a systematic search done on selected online databases (Google scholar, Scopus, Web of Sciences, and PubMed) and thereafter, data were extracted and analyzed using OpenMEE software. A random‐effects model was used and presented as standardized mean difference (SMD) at a 95 % confidence interval (CI). Sources of heterogeneity were explored by subgroup and meta-regression analysis using moderators variables (broiler strains, inclusion levels, age, and sex). The results showed that dietary GP did not affect FI [SMD = -0.13; P < 0.001; I2 = 89 %], ADG [SMD = -0.14; P < 0.001; I2 = 80 %] and FCR [SMD = 0.00; P < 0.001; I2 = 85 %] of broilers. Likewise, dressing percentage, breast, thigh, heart, and spleen weights in broiler chickens were not significantly affected. However, the weights of drumstick and gizzard were higher while liver weights were lower in broilers fed GP-based diets compared to those fed diets without GP. Regarding meat colour, broilers fed GP-based diets had higher meat redness compared to control. Meta-regression analysis revealed that broiler strains accounted for the most heterogeneity. In conclusion, dietary GP improved carcass traits and internal weight drumstick, gizzard weight, and meat redness in broiler chickens but had no effect on growth performance. Therefore, it is recommended that further investigation should be carried out to determine the optimal inclusion level of GP that support growth performance and liver weight in broiler chickens using optimisation model.